The Relationship Between Parenting Style and Social Maturity of Students at Integrated Islamic Junior High School X - Tulaila, Fittra; Fikry, Zulian (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to examine the relationship between parenting styles and the social maturity of students. The research design used in this study is correlational quantitative. The population of this study is students from the Sekolah Menengah Pertama Islam Terpadu X. The sampling technique used is total sampling, resulting in a total of 83 respondents. Data collection was conducted using the Parenting Style and Dimensions Questionnaire-Short Version (PSDQ-Short Version) and the Vineland Social Maturity Scale (VSMS). The data analysis technique used was the Product Moment Pearson Correlation analysis. Based on the hypothesis results, a p-value of 0.004 was obtained, which is less than 0.05, and an r-value of 0.310, indicating that there is a relationship between parenting style and the social maturity of students. Authoritative parenting is positively related to social maturity, while authoritarian and permissive parenting have a negative relationship with social maturity.